Проблема відповідності сучасної діловодної термінології відомствам та посадам давньоримської імперської канцелярії - Олійник, Микола; Федоров, Олександр (Видавництво Львівської політехніки, 2025)
When studying the clerical services of Ancient Rome, one can often encounter the problem of the correspondence of modern terminology to the analogous Latin one that existed in ancient times. This is especially often the case when studying foreign works on this topic, when there is a discrepancy in the nomenclature. That is, it would seem that over the period of almost two centuries of studying the administrative institutions of Ancient Rome, a single clerical terminology should have developed in the scientific community, which would relate to the general titles of positions for officials of state departments and their places of work. However, most modern scholars continue to use exclusively Latin terminology, avoiding equivalents from their native languages, such as German or English. The only exception was French historiography, whose representatives developed a single nomenclature that related to the central institutions of Ancient Rome.
Keywords: відомство; номенклатура; канцелярія; секретар; Стародавній Рим